2016
DOI: 10.3390/ma9120970
|View full text |Cite
|
Sign up to set email alerts
|

On the Sr1−xBaxFeO2F Oxyfluoride Perovskites: Structure and Magnetism from Neutron Diffraction and Mössbauer Spectroscopy

Abstract: Four oxyfluorides of the title series (x = 0.00, 0.25, 0.50, 0.75) have been stabilized by topotactic treatment of perovskite precursors Sr1−xBaxFeO3−δ prepared by soft-chemistry procedures, yielding reactive materials that can easily incorporate a substantial amount of F atoms at moderate temperatures, thus avoiding the stabilization of competitive SrF2 and BaF2 parasitic phases. XRD and Neutron Powder Diffraction (NPD) measurements assess the phase purity and yield distinct features concerning the unit cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…While an orthorhombic structure is reported for SrFeO 2 F, we considered that it was cubic in this study because any diffractions indicating the orthorhombic structure were not observed in the SXRD pattern. An inspection of the refinement results reveals that the thermal displacement parameters for the Fe 3+ ion and the anions decrease and increase, respectively, with decreasing x , consistent with the results reported in a previous study of Sr 1– x Ba x FeO 2 F . The variation of the thermal displacement parameter is shown in Figure A.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…While an orthorhombic structure is reported for SrFeO 2 F, we considered that it was cubic in this study because any diffractions indicating the orthorhombic structure were not observed in the SXRD pattern. An inspection of the refinement results reveals that the thermal displacement parameters for the Fe 3+ ion and the anions decrease and increase, respectively, with decreasing x , consistent with the results reported in a previous study of Sr 1– x Ba x FeO 2 F . The variation of the thermal displacement parameter is shown in Figure A.…”
Section: Resultssupporting
confidence: 88%
“…As Fe-containing oxyfluoride perovskites are interesting compounds from the perspectives of both fundamental and applied research, numerous compounds, including A FeO 2 F ( A = Pb, Ba, Sr), PbFe 0.5 Ti 0.5 O 2 F, 3 Sr 1– x BaFeO 2 F, La 1– x SrFeO 3– x F x , , 6H-BaFeO 2 F,15R-BaFeO 2 F, AgFeOF 2, and La 1– x Sr x Fe 1– y Co y O 3−δ have been synthesized, and their structure, magnetic properties, and photocatalytic activity have been investigated . BaFeO 2 F is particularly attractive because its tolerance factor is greater than unity, which indicates that it is potentially a ferroelectric material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation